Benito Mussolini - Roberts, Jeremy, 1956- (Biography (Twenty-First Century Books (Firm)), 2006)
Tells the life story of Italian dictator Benito Mussolini, describing his childhood in northern Italy, early exposure to politics, creation of the Fascist Party and rise to power in the 1920s, repressive regime, relationship with Adolf Hitler, and actions during World War II.